2020
DOI: 10.22452/mjcs.vol33no4.5
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Arabic Sign Language Recognition: A Review, Taxonomy, Open Challenges, Research Roadmap and Future Directions

Abstract: Sign language is still the best communication mean between the deaf and hearing impaired citizens. Due to the advancements in technology, we are able to find various research attempts and efforts on Automatic Sign Language Recognition (ASLR) technology for many languages including the Arabic language. Such attempts have simplified and assisted the interpretation between spoken and sign languages. In fact, the technologies that translate between spoken and sign languages have become popular today. Being the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
0
8
1
Order By: Relevance
“…Opposite than other studies, the results indicated that the device has some issues. While previous studies [2], [12] claimed that the device has a great potential, our results reveal that the device has its limitations. When comparing between the studies, we found that the previous studies have focused on specific letters or context that are performed only by hands.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Opposite than other studies, the results indicated that the device has some issues. While previous studies [2], [12] claimed that the device has a great potential, our results reveal that the device has its limitations. When comparing between the studies, we found that the previous studies have focused on specific letters or context that are performed only by hands.…”
Section: Discussioncontrasting
confidence: 68%
“…Recently, much research has been conducted on the use of leap motion controllers to detect and deal with ArSL [12]. Despite the momentum of using leap motion controllers to deal with ArSL, we have concerns about the correctness or completeness of the generated results.…”
Section: Introductionmentioning
confidence: 99%
“…If a deaf individual attempts to express anything, they employ gestures for communication. Every symbol indicates a special letter, emotion, or word [7]. A stage was formed by signal combination, and a string of words invokes letters in spoken languages.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many experts and scholars have conducted continuous and in-depth research on SLR methods and convolutional neural networks, and have achieved fruitful results. For example, researchers such as Al-Shamayleh A S proposed a very compact in-place gated CRNN for end-to-end multi-channel speech enhancement, which utilizes in-place convolution for frequency pattern extraction and reconstruction, in-place The features effectively preserve spatial cues in each frequency bin, and utilize a novel spectral restoration method to effectively improve speech quality by predicting magnitude masks, mappings, and phases [6]. Researchers such as Saleh BM proposed a robust SLR method based on deep learning, which represented multimodal information through texture maps to describe hand position and motion, and used this information as the basis for two three-stream and two-stream CNN models.…”
Section: Introductionmentioning
confidence: 99%